Caracterización cromohipológica y zoométrica de los caballos criollos en la provincia de Manabí (Fase II) - Vélez Valdez, Oscar Stalin (2021)
The objective of this research was to characterize the criollo horses present in 24 de Mayo canton, Manabí province through chromohipology and zoometry. For this, 125 horses of different ages and sexes were used. The data were analyzed with the statistical package InfoStat (2020). A descriptive statistical analysis was carried out; The following zoometric variables were determined: head length and width 52.23 (± 3.45) cm and 19.15 (± 1.54) cm respectively; croup length and width 43.28 (± 2.96) cm and 40.67 (± 3.43) cm in their order; height of the withers and rump 131.71 (± 6.40) cm and 131.92 (± 6.33) cm correspondingly; longitudinal diameter 133.89 (± 6.93) cm; dorso-sternal 59.34 (± 4.62) cm; bicostal 32 (± 4.05) cm; thoracic circumference 152.32 (± 8.73) cm; cane 16.86 (± 1.25). The zoometric indices calculated show the horse as brachycephalic (57.00%), longlinear (40.00%), dolichothoracic (63.00%), dolichomorphic (49.00%), low metacarpal correlation (48.00%), brachypelvic (69.00%), and long proportionality (50.00%), the mare as mesocephalic (43.00%), longlinear (55.00%), brachytaracic (52.00%), dolichomorphic (52, 00%), low metacarpal correlation (52.00%), brachypelvic (76.00%), and long proportionality (58.00%). With respect to the chromohypological variables, they show that the chestnut coat obtained a higher frequency with (51.00%), likewise the majority with black helmets with (49.00%), (85.00%) with a rectilinear head profile, (83.00%) cervical pyramidal profile, (81.00%) normal dorso-lumbar profile and (75.00%) normal ventral profile. It is concluded that the evaluated horses have chromohypological and zoometric characteristics that frame them as an Ecuadorian creole horse, these results allow them to be related to the research already carried out in Manabí province and the Ecuadorian mountains.